Driving Influences of the Doppler Flash Observed by SuperDARN HF Radars in Response to Solar Flares - Chakraborty, S. (2022)
Sudden enhancement in high-frequency absorption is a well-known impact of solar flare-driven Short-Wave Fadeout (SWF). Less understood, is a perturbation of the radio wave frequency as it traverses the ionosphere in the early stages of SWF, also known as the Doppler flash. Investigations have suggested two possible sources that might contribute to it’s manifestation: first, enhancements of plasma density in the D-and lower E-regions; second, the lowering of the F-region reflection point. Our recent work investigated a solar flare event using first principles modeling and Super Dual Auroral Radar Network (SuperDARN) HF radar observations and found that change in the F-region refractive index is the primary driver of the Doppler flash. This study analyzes multiple solar flare events observed across different SuperDARN HF radars to determine how flare characteristics, properties of the traveling radio wave, and geophysical conditions impact the Doppler flash. In addition, we use incoherent scatter radar data and first-principles modeling to investigate physical mechanisms that drive the lowering of the F-region reflection points. We found, (a) on average, the change in E- and F-region refractive index is the primary driver of the Doppler flash, (b) solar zenith angle, ray’s elevation angle, operating frequency, and location of the solar flare on the solar disk can alter the ionospheric regions of maximum contribution to the Doppler flash, (c) increased ionospheric Hall and Pedersen conductance causes a reduction of the daytime eastward electric field, and consequently reduces the vertical ion-drift in the lower and middle latitude ionosphere, which results in lowering of the F-region ray reflection point.